Vesicouterine Fistula in Burkina Faso: Report of 36 Cases in a Multicentric Study - Boureima Ouedraogo; Brahima Kirakoya; Moussa Kabore; Adama Millogo; Adama Ouattara; Fasnewinde Aristide Kabore (Société Internationale d’Urologie Journal)
ObjectiveTo report etiological and therapeutic features of vesicouterine fistulas (VUF) in Burkina Faso.Patients and MethodsWe performed a retrospective, descriptive, and multicentric study based on the medical records of women treated for VUF from January 2010 to December 2016. ResultsVUF accounted for 7.2% (36/497) of urogenital fistulas managed during the study period. The median age of the 36 patients was 35 years (interquartile range = 27 to 37.5 years) with values ranging from 16 years to 64 years old. Among VUF, obstetric fistula accounted for 26 cases (26/36) versus 10 cases (10/36) of iatrogenic fistula. Obstetric VUF were consecutive to emergency Caesarean section (n = 16) and vaginal delivery (n = 10) after prolonged obstructed labor. The 10 cases of iatrogenic VUF were subsequent to prelabour Caesarean section. The main circumstance of VUF occurrence was Caesarean section (26/36). In 10 cases (10/36), VUF was associated with a vesicovaginal fistula. Thirty days after the removal of the catheter, the success rate fell from 89% to 80.6%. ConclusionVUF is rare but its frequency is not negligible in our context. The main circumstance of occurrence remains Caesarean section. The best treatment remains prevention